Wittig-horner approach for the synthesis of tamoxifen - Pandey, RK; Wakharkar, RD; Kumar, P (Synthetic Communications, 2005)
A stereoselective synthesis of Z -tamoxifen, a tetra-substituted alkene with antiestrogenic activity, is described. The Wittig-Horner reaction has been employed as the key step to establish the olefin stereochemistry.
Keywords: anticancer drug; phosphonate; stereoselectivity; Tamoxifen; Wittig-Horner reaction